EPIDEMIOLOGY OF RABIES IN DOGS IN BRAZIL: CHALLENGES IN CONTROL AND PREVENTION (International Seven Journal of Multidisciplinary, 2025)
Objective: To analyze the epidemiology of rabies in dogs in Brazil, identifying the challenges in the control and prevention of the disease, with emphasis on changes in the epidemiological profile, the interaction between the urban and wild cycles, and the effectiveness of vaccination and epidemiological surveillance strategies. Rabies is a highly lethal viral zoonosis, caused by the genus Lyssavirus, and is historically associated with transmission by domestic dogs. With the progress of vaccination campaigns, rabies cases in the urban cycle have decreased considerably, while the role of the wild cycle, particularly of hematophagous bats and wild canids, has been gaining greater importance. Immunization against rabies is still the main control strategy, however, obstacles such as low vaccination coverage, growth in the number of stray dogs, and failures in case notification complicate the elimination of the disease. The interaction between domestic dogs and wild animals constitutes a danger for the reintroduction of rabies in the urban environment, requiring joint measures of population control, education and new strategies, such as the application of oral vaccines in wild reservoirs. It is essential to reinforce public policies, such as intensifying vaccination campaigns to prevent and eradicate rabies in Brazil.